Identifying the professional development Initiatives for building teachers capacities and skills for 21st century education in Nigeria (2023)
Teacher professional development refers to programs, which focused on continuing education effort for educators. The goal is to provide teachers with opportunities to continue to improve their skills and learn new strategies and techniques, thereby leading to better student outcomes in the 21st century classroom situation. However, the initiative towards teacher capacity building is not well conceived. Previous studies on teacher professional development initiatives more of political approach than on scientific approach. This study therefore identified the professional development initiatives for building teachers' capacities and skills for 21st century education in Nigeria. As it has been claimed that 21st century acting as an active force behind the rapid transition of education. The whole world is moving fast to make permanent impression in the world of knowledge. As the 21st century has brought about quantitative and qualitative changes in all the disciplines of knowledge. But we cannot ripe the fruits of such occurred and occurring transformations until we have professionally developed and trained teachers in our education system. Therefore, it appears to be crucial that teacher professional development programmes equip the teachers we need for education with the necessary skills to achieve the education expectations we want in the 21st Century education. This study highlighted effective methods of teacher professional development for 21st century education and emphasized the positive impact on the growth and development of teachers. Major discussions of the paper are education we need in the 21st century skills, the professional development initiatives that teachers need for 21st century education, responsibilities of teachers, theoretical support and professional development of teachers and their significance. The paper recommends among others that critical thinking, problem solving, communication and collaboration, cross-cultural understanding, creativity and innovation, information literacy, media literacy, technology and ICT literacy should be included in the teacher preparation programme.